Qu’imite-t-on dans une traduction ? - Camille Fort (Sillages Critiques)
That translation should attempt to be mimetic in its hope to restitute the original will not be denied. However, its history shows that « imitation » is a floating signifier, appropriated in turn by the champions of literalism and the partisans of free textual recreation. We may wonder, then, what it is that is imitated in translation – an arrangement of words and ideas or an intent to communicate ? To answer this question, we shall remember the French translators of Aristotle’s Poetics and their decision to translate mimesis as « representation ». To imitate, for a translator, comes akin to re-representing the text, investing in it a speech effect equivalent to that which it produced upon its initial reception. The translator will not attempt to delete what, in the text, constitutes a testimony to or dialogue with the linguistic and literary conventions of the time, but they will bring the text into a certain present – that of the aesthetic event. They will enact what Antoine Berman calls « a non perceptible resemblance », letting the force of the text become manifest beyond mere semantic conversions.